2021
DOI: 10.1016/j.molmet.2021.101174
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic hormone-sensitive lipase regulates appetite and energy homeostasis

Abstract: Objective The goal of this study was to investigate the importance of central hormone-sensitive lipase (HSL) expression in the regulation of food intake and body weight in mice to clarify whether intracellular lipolysis in the mammalian hypothalamus plays a role in regulating appetite. Methods Using pharmacological and genetic approaches, we investigated the role of HSL in the rodent brain in the regulation of feeding and energy homeostasis under basal conditions during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 62 publications
3
6
0
Order By: Relevance
“…For the first time, to our knowledge, we demonstrate here that HSL is necessary for memory performance, since the HSL −/− mouse exhibited impaired short-term and long-term memory in the Barnes maze as well as impaired spatial working memory in the Y-maze. This role of HSL in cognition adds up to previous suggestions of HSL-mediated lipolysis modulating hypothalamic function ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 79%
“…For the first time, to our knowledge, we demonstrate here that HSL is necessary for memory performance, since the HSL −/− mouse exhibited impaired short-term and long-term memory in the Barnes maze as well as impaired spatial working memory in the Y-maze. This role of HSL in cognition adds up to previous suggestions of HSL-mediated lipolysis modulating hypothalamic function ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 79%
“…For the first time to our knowledge, we demonstrate here that HSL is necessary for memory performance, since the HSL-/-mouse exhibited impaired short-and long-term memory in the Barnes maze, as well as impaired spatial working memory in the Y-maze. This role of HSL in cognition adds up to previous suggestions of HSL-mediated lipolysis modulating hypothalamic function (Sekiya et al, 2004;Hundahl et al, 2021).…”
Section: Discussionsupporting
confidence: 75%
“…CREB was a transcription factor known to play an important role in the osteocalcin-regulated ATP production by modulating glucose uptake and myofibrillar glycolysis . HSL was a key rate-limiting enzyme, which helped to hydrolyze intracellular triglycerides into free fatty acids in muscles . Moreover, western blotting also showed that PCPY-1 apparently increased the protein levels of p-CREB and p-HSL in the BMSCs/C2C12 co-culture system, compared with the control group and the BMSCs/C2C12 co-culture system without PCPY-1 (Figure G–I).…”
Section: Resultsmentioning
confidence: 99%